Aerococcus urinae: Severe and Fatal Bloodstream Infections and Endocarditis - de Jong, Margriet F. C. (American Society for Microbiology (ASM), 2010)
Aerococcus urinae is a pathogen that rarely causes severe or fatal infections. We describe four cases of severe A. urinae bloodstream infections. All patients had underlying urologic conditions. Urine cultures, however, were negative.